2012
DOI: 10.1371/journal.pone.0050632
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vaginal SHIV Transmission in Macaques by a Coitally-Dependent Truvada Regimen

Abstract: BackgroundDaily pre-exposure prophylaxis (PrEP) with Truvada (a combination of emtricitabine (FTC) and tenofovir (TFV) disoproxil fumarate (TDF)) is a novel HIV prevention strategy recently found to prevent HIV transmission in men who have sex with men and heterosexual couples. We previously showed that a coitally-dependent Truvada regimen protected macaques against rectal SHIV transmission. Here we examined FTC and tenofovir TFV exposure in vaginal tissues after oral dosing and assessed if peri-coital Truvada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 36 publications
3
76
0
Order By: Relevance
“…However, the larger volume applied (3 ml) and the higher FTC gel concentration (5%) implemented in those previous studies collectively increased the total drug dosage, which may account for the higher drug concentrations in vivo. Higher plasma concentrations of FTC and TFV have also been reported for pigtailed macaques receiving oral FTC-TDF at a dose equivalent to that in humans (20 mg/kg of body weight of FTC and 22 mg/kg TDF) (33). However, the peak levels of drugs secreted in vaginal fluids in macaques following oral tablet treatment are 2 to 3 orders of magnitude lower than the concentrations of FTC and TFV observed 24 h after vaginal RDT application reported here, suggesting that the RDT might be a more effective, and potentially safer, delivery method than oral PrEP.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the larger volume applied (3 ml) and the higher FTC gel concentration (5%) implemented in those previous studies collectively increased the total drug dosage, which may account for the higher drug concentrations in vivo. Higher plasma concentrations of FTC and TFV have also been reported for pigtailed macaques receiving oral FTC-TDF at a dose equivalent to that in humans (20 mg/kg of body weight of FTC and 22 mg/kg TDF) (33). However, the peak levels of drugs secreted in vaginal fluids in macaques following oral tablet treatment are 2 to 3 orders of magnitude lower than the concentrations of FTC and TFV observed 24 h after vaginal RDT application reported here, suggesting that the RDT might be a more effective, and potentially safer, delivery method than oral PrEP.…”
Section: Discussionmentioning
confidence: 76%
“…This is likely due to several constraints, including limited biopsy sample sizes, relatively high lower limits of quantitation (100 to 500 ng/g for TFV-DP and 30 to 60 ng/g for FTC-TP, also affected by sample size), and the commonly reported difficulties in stabilizing these metabolites following sample collection and processing. Previous macaque studies that reported intracellular vaginal TFV-DP and/or FTC-TP levels employed terminal PK study designs allowing the collection of large tissue samples and the isolation of vaginal lymphocytes (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…Oral Truvada has been evaluated for safety and PrEP efficacy in vaginal HIV prevention in several clinical trials (54) and has shown 73% protection in heterosexual serodiscordant couples with adherence rates of 90% or more (4). Oral daily dosing of TDF-FTC was found to completely protect six pig-tailed macaques from infection using a repeatedexposure vaginal SHIV transmission model with 18 weekly exposures, spanning 4 menstrual cycles, to low doses of SHIV162p3 (55). The median maximal concentration (C max ) values for TFV and FTC in vaginal fluid samples were found to be 1.14 g ml Ϫ1 and 7.23 g ml Ϫ1 , respectively, several orders of magnitude lower than the steady-state concentrations reported here (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Data from clinical trials has shown that patients with detectable plasma drug levels indicative of adherence have reduced risk of HIV-1 infection, while poor PrEP adherence confers little protection (2,4,(6)(7)(8). Although recent work suggests that sexual event-driven TDF-FTC administration can be effective in men (9)(10)(11), sporadic PrEP adherence can lower PrEP efficacy and promote selection of drug-resistant variants. To reduce pill burden, long-acting injectable nanoparticle formulations of the nonnucleoside reverse transcriptase inhibitor (NNRTI) rilpivirine (RPV) and an experimental integrase inhibitor, cabotegravir, have been developed (12,13).…”
mentioning
confidence: 99%